A review on the applications of nanofluids in solar energy systems. (March 2015) - Kasaeian, Alibakhsh; Eshghi, Amin Toghi; Sameti, Mohammad
Abstract: The negative impact of human activities on the environment receives tremendous attention, especially on the increased global temperature. To combat climate change, clean and sustainable energy sources need to be rapidly developed. Solar energy technology is considered as one of the ideal candidates, which directly converts solar energy into electricity and heat without any greenhouse gas emissions. In both areas, high-performance cooling, heating and electricity generation is one of the vital needs. Modern nanotechnology can produce metallic or nonmetallic particles of nanometer dimensions which have unique mechanical, optical, electrical, magnetic, and thermal properties. Studies in this field indicate that exploiting nanofluid in solar systems, offers unique advantages over conventional fluids. In this paper, the applications of nanofluids on different types of solar collectors, photovoltaic systems and solar thermoelectrics are reviewed. Beside the wide range of energy conversion, the efforts done on the energy storage system (ESS) have been reviewed. In the field of economics, nanotech reduces manufacturing costs as a result of using a low temperature process.